A finite element phase field model for relaxor ferroelectrics. Issue 1 (21st October 2015) - Xu, Bai‐Xiang; Wang, Shuai; Yi, Min
Abstract: A mechanically coupled phase field model is presented for the domain evolution and mesoscopic response of relaxor ferroelectrics. In the model the spontaneous polarization is treated as order parameter. The model is derived from thermodynamic analysis including the material force theory. Random field theory is adopted to take the disorder of relaxor ferroelectrics into account. Results show that the model is capable of reproducing relaxor features, such as domain miniaturization, small remnant polarization and large piezoelectric response. Dependence of these features on the random field strength is discussed. (© 2015 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)